2022
DOI: 10.1186/s13102-022-00411-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cardiorespiratory fitness, fatness, hemodynamic characteristics, and sedentary behaviour in primary school-aged children

Abstract: Background Low cardiorespiratory fitness (CRF) is associated with the development of cardiovascular diseases during childhood, adolescence and older ages. The purpose of the study was to investigate associations between fatness, hemodynamic characteristics and secondary time with CRF in primary school-aged children. Methods Height, weight, body mass index (BMI), blood pressure (BP), heart rate (HR), CRF (20 m shuttle-run) and sedentary time were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…As in the Norwegian study, also we found that a lower body mass index was associated with higher VO2 peak/kg in JIA patients [13]. A recent study by Pepera et al 2022 observed that healthy children with a normal BMI had better CRF than obese and overweight children [44]. In 2010, Goran et al reported that the major influence of body weight on VO2 peak is explained by fat free mass and that excess fatness has a detrimental effect on submaximal aerobic capacity [45].…”
Section: Discussionsupporting
confidence: 75%
“…As in the Norwegian study, also we found that a lower body mass index was associated with higher VO2 peak/kg in JIA patients [13]. A recent study by Pepera et al 2022 observed that healthy children with a normal BMI had better CRF than obese and overweight children [44]. In 2010, Goran et al reported that the major influence of body weight on VO2 peak is explained by fat free mass and that excess fatness has a detrimental effect on submaximal aerobic capacity [45].…”
Section: Discussionsupporting
confidence: 75%
“…To date, the majority of results from research support previously published results concerning the negative impact of high %BF on both aerobic and anaerobic fitness related components in 10- to 12-year-old school-aged team handball players in Qatar [ 41 ]. Previous reports confirm that correlations exist between fatness, physical fitness, and academic performance in pre-pubertal handball children in Qatar [ 22 , 23 , 24 ]. In addition, the results of Hermassi et al [ 22 ] show that both BMI and %BF were negatively correlated with academic performance of schoolchildren handball players.…”
Section: Introductionmentioning
confidence: 69%
“…There is a well-described positive association between academic attainment and physical fitness [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], which justifies school-based physical activity programs with the joint aim of increasing physical fitness and academic attainment in schoolchildren. Specifically, the positive relationship between cardiorespiratory fitness and academic achievement has attracted considerable attention in the last decade [ 21 , 22 , 23 , 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As obesity and the sedentary lifestyle are becoming more prevalent, especially among the young population, cardiorespiratory functional evaluations are useful tools for assessing the fitness level. In recent studies, CRF has been proven to correlate negatively with parameters such as BMI and the sedentary lifestyle at younger ages [ 52 ].…”
Section: Discussionmentioning
confidence: 99%